Theology at the University of Pretoria - 100 years: (1917-2017) Past, present and future - Pilay, Jerry (Verbum et Ecclesia, 2017)
In this scholarly book, a century's theology presented by the Faculty of Theology at the University of Pretoria, is celebrated. All authors are academics or research associates of the University of Pretoria. A historical and futuristic overview with perspectives from the past, present and future, are examined. The past is not only portrayed by means of societal and scientific contributions and achievements, but the authors also reflect on malfunctions, ill behaviour and disappointments of church and theology, presented at the University of Pretoria within the South African context over 100 years. The book commences with a chapter in which institutional transformation is discussed, as well as the changes that demonstrate the role of the Faculty of Theology within a secular state university. It includes an explanation of the importance of research impact, research productivity and research reputation. Among various discipline indicators, the category Theology and Religion Studies plays a significant role in the measurement of world university rankings of universities. With regard to scientific and encyclopaedic content, the book focuses on the theological disciplines presented in the academic curricula: first the biblical sciences (Old and New Testament Studies), then the historical disciplines (Systematic Theology, Church History and Church Polity), and finally the practical disciplines (Practical Theology, Science of Religion and Missiology). The role of Religion Studies in a newly established Faculty of Theology and Religion not only enhances the diversity of interreligious tolerance and an atmosphere of dialogue, but it serves as platform to interconnect with the fields of Humanities, Social and Natural Sciences and other academic disciplines. In the conclusive part of the book, contributions highlight the role of the centres in the Faculty (Centre for Contextual Ministry and Centre for Sustainable Communities), as well as the continental and international footprints of the two theological journals whose title ownership is attached to the Faculty of Theology of the University of Pretoria, namely HTS Theological Studies and Verbum et Ecclesia. The methodology comprised in all the chapters amounts to a literature and contextual study. Since the book describes the histories of formal academic departments, these texts are of a descriptive, interpretative and critical character. Reference is made in some chapters to exegetical methods, like the historical critical methods. The target audience of the book is academic scholars and theologians, who specialise in the different fields of Theology, the Humanities and other Social Sciences. The book is also accessible to scholars of other academic disciplines outside these disciplines. The book comprises original research by several authors and is not plagiarised from other scientific publications of this nature.